Geochemical and Isotopic Characteristics of Two Geothermal Systems at the Nanpu Sag, Northern Bohai Bay Basin - Wang, Ke; Hua, Cong; Ren, Lu; Kong, Yanlong; Sun, Wenjie; Pan, Sheng; Cheng, Yuanzhi; Huang, Yonghui; Tian, Fei; Zhang, Weizun; Qin, Dajun; Ma, Feng; et al. (Frontiers in Earth Science, 2022)
The utilization of geothermal energy has gradually increased in northern China because of its unique advantages as a heating supply. However, the sustainable exploitation of geothermal energy usually requires a comprehensive investigation of the geothermal water circulation pattern prevailing at a proposed site. During the exploitation of geothermal energy resources at Nanpu Sag in northern China, thermal anomalies were found to exist in two adjacent regions: the Caofeidian and the Matouying. To reconcile the anomalies and to examine both the source of recharge water and the geothermal systems’ circulation dynamics, a comprehensive investigation was performed using multiple chemical and isotopic tracers (δ2H, δ18O, 87Sr/86Sr, δ13C, and 14C). The total dissolved solids (TDS) of the geothermal water are approximately 750 mg/L and 1250 mg/L, respectively. The geothermal water isotopes at the two sites are also different, with average values of -9.3 ‰ and -8.2‰ for δ18O and -73.4‰ and -71‰ for δ2H, respectively. Moreover, the 87Sr/86Sr ratio of geothermal water at Matouying is 0.7185, which is much greater than that of Caofeidian, with an average value of 0.7088. All the results confirm the difference between the two geothermal sites and may explain the two circulation patterns of deep groundwater at Caofeidian and Matouying. The reservoir temperature obtained from theoretical chemical geothermometers is estimated to be 83-92℃ at the Caofeidian and 107-137℃ at the Matouying, respectively. The corrected 14C age implies a low circulation rate that would allow sufficient time to heat the water in the system. In addition, we propose a geothermal system conceptual model in our study area. This model could provide key information regarding the geothermal system's sustainability and the effective management of geothermal resources.